TEKS KLASIK SEBAGAI SUMBER PENGEMBANGAN LEKSIKOGRAFI MINANGKABAU - Rona Almos; Pramono Pramono; Herry Nur Hidayat; Seswita Seswita (Universitas Andalas, 2017)
The extinction of regional languages is a phenomenon that needs to be examined and addressed seriously and wisely. Minangkabau language is also feared to be extinct. The Minangkabau language has undergone a change that occurs in the direction of reducing vocabulary. Classic vocabulary, for example, has been replaced by a new vocabulary and even completely disappeared.This study will specifically find out the kinds of Minangkabau classical texts originating from text edits. Data sources were obtained from the results of research on philology and folklore, namely the edits of manuscripts and folklore documentation. The Lexicon of Minangkabau classical texts in this paper are grouped into three groups, namely, nouns, verbs, and adjectives. Keywords: classical text, Minangkabau, vocabulary, manuscript